IDO activity forecasts obesity in males and premenopausal females in a 10-year follow-up study:The Cardiovascular Risk in Young Finns Study - Niinisalo Petri; Raitakari Olli T; Kähönen Mika; Hurme Mikko; Lehtimäki Terho; Magnussen Costan; Viikari Jorma; Juonala Markus; Kaaja Risto (ELSEVIER IRELAND LTD, 2022)
Background and aims: Indoleamine 2,3-dioxygenase (IDO) is an intracellular enzyme associated with artery wall inflammation. Previous studies have verified correlation between IDO activity and early signs of atherosclerosis especially in females. We aimed to elucidate the relationship between an estimate of IDO activity and atherosclerotic risk factors related to non-alchohol-fatty liver (NAFLD) in a 6- and 10-year follow-up.
Methods: Estimates of IDO activity along with complete risk factor data were measured from females (n = 506; age 24-39) and males (n = 421; age 24-39) in 2001. Risk factor measurements were conducted again in 2007 and 2011. Statistical examinations were carried out by Pearson correlation and risk ratio analysis.
Results: In females, age-adjusted IDO correlated with body mass index (BMI) (p = 0.0008), waist (p = 0.0009), C reactive protein (CRP) (p = 0.0014) and logarithmically modified triglycerides (p = 0.0488) in 2007. Correlation remained significant with BMI (p = 0.0007) and waist (p = 0.0063) in 2011. In males, age-adjusted IDO correlated with waist (p = 0.0367) and high-density lipoprotein cholesterol (HDL-C) (p = 0.0489) in 2007. Correlation remained significant with HDL-C (p = 0.0348) in 2011. In risk ratio analysis, relationship between IDO and obesity was confirmed in females after 10 years (RR = 1.026, p = 0.0147, 95% CI) and in males after 6 and 10 years (RR = 1.019, p = 0.0091, 95% CI and RR = 1.015, p = 0.0404, 95% CI, respectively) when the data was adjusted for age and BMI.Conclusions: IDO activity correlated with obesity and factors related to NAFLD, namely obesity of visceral type, hypertriglyceridemia and CRP (in females), well-characterized risk factors for diabetes and atherosclerosis in 6 and 10-year follow-up in males and premenopausal females.